2010
DOI: 10.1038/npp.2010.175
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release d-Amphetamine Reduces Cocaine but not ‘Speedball’-Seeking in Buprenorphine-Maintained Volunteers: A Test of Dual-Agonist Pharmacotherapy for Cocaine/Heroin Polydrug Abusers

Abstract: The aim of this study was to determine whether oral sustained release d-amphetamine (SR-AMP) reduces cocaine and opioid/cocaine combination (‘speedball’-like) seeking in volunteers with current opioid dependence and cocaine dependence. Following outpatient buprenorphine (BUP) 8mg/day stabilization without SR-AMP, 8 participants completed a 3-week inpatient study with continued BUP 8 mg/day maintenance and double-blind ascending SR-AMP weekly doses of 0, 30 and 60 mg/day, respectively. After 3 days (Sat–Mon) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 77 publications
5
70
0
Order By: Relevance
“…These initial findings have been replicated and extended by us (Banks et al, 2013b), by other investigators working with other schedules of cocaine self-administration in nonhuman primates (Czoty et al, 2010;Czoty et al, 2011), and by investigators working with various schedules of cocaine self-administration in rats (Chiodo et al, 2008;Thomsen et al, 2012). In addition, amphetamine maintenance decreased cocaine vs money choice in human laboratory studies (Greenwald et al, 2010;Rush et al, 2010), and cocaine use by patients in placebo-controlled double-blind clinical trials (Grabowski et al, 2001;Mariani et al, 2012). Finally, recent meta-analyses of clinical studies have highlighted agonist medications in general, and amphetamine maintenance in particular, as superior in efficacy to many other drug classes as candidate medications for treatment of cocaine dependence (Amato et al, 2007;Amato et al, 2011;Castells et al, 2010;Minozzi et al, 2008;Pani et al, 2011a;Pani et al, 2011b).…”
Section: Evidence For Therapeutic Efficacy Of Ago-nist Medications Tomentioning
confidence: 65%
“…These initial findings have been replicated and extended by us (Banks et al, 2013b), by other investigators working with other schedules of cocaine self-administration in nonhuman primates (Czoty et al, 2010;Czoty et al, 2011), and by investigators working with various schedules of cocaine self-administration in rats (Chiodo et al, 2008;Thomsen et al, 2012). In addition, amphetamine maintenance decreased cocaine vs money choice in human laboratory studies (Greenwald et al, 2010;Rush et al, 2010), and cocaine use by patients in placebo-controlled double-blind clinical trials (Grabowski et al, 2001;Mariani et al, 2012). Finally, recent meta-analyses of clinical studies have highlighted agonist medications in general, and amphetamine maintenance in particular, as superior in efficacy to many other drug classes as candidate medications for treatment of cocaine dependence (Amato et al, 2007;Amato et al, 2011;Castells et al, 2010;Minozzi et al, 2008;Pani et al, 2011a;Pani et al, 2011b).…”
Section: Evidence For Therapeutic Efficacy Of Ago-nist Medications Tomentioning
confidence: 65%
“…One example of this pharmacotherapy approach is studies with the dopamine/norepinephrine-selective releaser d-amphetamine. Chronic d-amphetamine treatment produced dose-dependent and sustained decreases in cocaine self-administration under second-order, progressive-ratio, and concurrent drug vs food schedules of reinforcement in rats (Chiodo et al, 2008;Thomsen et al, 2012), nonhuman primates (Czoty et al, 2011;Negus, 2003;Negus and Mello, 2003), and/or humans (Greenwald et al, 2010;Rush et al, 2010). Overall, these studies demonstrate that cocaine self-administration in general, and cocaine vs food choice in particular, is sensitive to pharmacological manipulations.…”
Section: Introductionmentioning
confidence: 65%
“…Thus, in preclinical studies that aspire to evaluate pharmacological or behavioral treatment strategies for drug dependence, choice procedures can play a critical role in the preclinical evaluation process to determine whether a given experimental manipulation produces this critical reallocation of behavior (Haney and Spealman, 2008;Negus et al, 2011). Second, although dopamine/norepinephrine-selective releasers have consistently demonstrated efficacy to decrease cocaine choice in nonhuman primates Negus, 2003;present study), human laboratory studies (Greenwald et al, 2010;Rush et al, 2010), and clinical trials (Grabowski et al, 2001;Mooney et al, 2009), the magnitude of this therapeutic effect is limited by untoward effects and lower than the magnitude of effect that can potentially be achieved with behavioral economic approaches. However, the present results suggest that phenmetrazine or related compounds may nonetheless be therapeutically useful under circumstances in which cocaine is relatively inexpensive, cocaine consumption is maintained by relatively low cocaine doses, and behavioral options are limited.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding agonist replacement therapy, several clinical studies involving d-amphetamine (potentially associated with treatment duration and/or dose) documented reductions in cocaine-seeking behavior or use (Grabowski et al, 2004;Greenwald, Lundahl, & Steinmiller, 2010;Rush, Stoops, & Hays, 2009;Shearer, Wodak, van Beek, Mattick, & Lewis, 2003). A singular RCT of immediate-and sustained-release methamphetamine indicated that the latter formulation reduced cocaine craving and use (Mooney et al, 2009).…”
Section: Pharmaco-therapeutic Interventionsmentioning
confidence: 99%